2016
DOI: 10.1002/ange.201602235
|View full text |Cite
|
Sign up to set email alerts
|

Short, Enantioselective Total Synthesis of Highly Oxidized Taxanes

Abstract: In the realm of natural product chemistry, few isolates have risen to the level of fame justifiably accorded to Taxol (1) and its chemical siblings. This report describes the most concise route to date for accessing the highly oxidized members of this family. As representative members of taxanes containing five oxygen atoms, decinnamoyltaxinine E (2) and taxabaccatin III (3), have succumbed to enantioselective total synthesis for the first time in only 18 steps from a simple olefin starting material. The strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…In conclusion, we were able to perform the synthesis of a key synthetic precursor (5) of tetracyclic aspochalasan natural products and derivatives, the structure of which could be confirmed by X-ray analysis of an epoxide product (26). Compound 5 constitutes a good entry to perform the "oxidase" phase in the bio-inspired synthesis of natural products such as trichoderone A (3) and trichodermone (4). In particular, this work constitutes a formal synthesis of 3.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…In conclusion, we were able to perform the synthesis of a key synthetic precursor (5) of tetracyclic aspochalasan natural products and derivatives, the structure of which could be confirmed by X-ray analysis of an epoxide product (26). Compound 5 constitutes a good entry to perform the "oxidase" phase in the bio-inspired synthesis of natural products such as trichoderone A (3) and trichodermone (4). In particular, this work constitutes a formal synthesis of 3.…”
mentioning
confidence: 72%
“…General remarks (1S,2R)-1,2-Dihydroxy-1-methylcycloheptane (13) (2S)-2-Trimethylsilyloxy-2-methylcycloheptan-1-one (15) (7S)-7-Hydroxy-7-methyl-1-trifluoromethanesulfonyloxycyclohept-1-ene (12) (7S)-7-Acetoxy-7-methyl-1-trifluoromethanesulfonyloxycyclohept-1-ene (16) (7S)-7-Acetoxy-7-methyl-1-[(1E,3E)-3-methylpenta-1,3-dien-1-yl]cyclohept-1-ene (10), as a 4:1 mixture with the 1Z isomer 1E,3E)-3-methylpenta-1,3-dien-1-yl)cyclohept-2-en-1-yl]acetyl}-3phenylselenyl-2-pyrrolidone (mixture of stereoisomers 23) (3S,3aR,4S,6aS,8aS,13bR)-5-Benzoyl-4-isobutyl-2,3,13-trimethyl-4,5,8,8a,9,10,11,12-octahydro-3Hcyclohepta [3,4]benzo [1,2-d]isoindole-6,7(3aH,13bH)-dione (endo product 24) (3R,3aR,4S,6aS,8aS,13bS)-5-Benzoyl-4-isobutyl-2,3,13-trimethyl-4,5,8,8a,9,10,11,12-octahydro-3Hcyclohepta [3,4]benzo [1,2-d]isoindole-6,7(3aH,13bH)-dione (exo product 25) (3S,3aR,4S,6aS,8aS,13bR)-4-Isobutyl-2,3,13-trimethyl-4,5,8,8a,9,10,11,12-octahydro-3H-cyclohepta [3,4]benzo [1,2d]isoindole-6,7(3aH,13bH)-dione (5) (3S,3aR,4S,6aS,8aS,13R,13aR,13bR)-5-Benzoyl-13,13a-epoxy-4-isobutyl-2,3,13-trimethyl-4,5,8,8a,9,10,11,12-octahydro-3Hcyclohepta [3,4]benzo [1,2-d]isoindole-6,7(3aH,13bH)-dione (26) (3S,3aR,4S,6aS,8aS,13S,13aS,13bR)-5-Benzoyl-13,13a-epoxy-4-isobutyl-2,3,13-trimethyl-4,5,8,8a,9,10,11,12-octahydro-3Hcyclohepta [3,4]…”
Section: Table Of Content Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Consideringt he yield andr eaction time, DABCO was employed as ab ase for further investigations.C ombining DABCO with acetic acid instead of TFAr esulted in al ower yield (entry 13). Various oxidation conditions, including H 2 O 2 / HCO 2 H, [18] MoO 5 ·pyridine complex, [19] and PhNO, [20] were tested, but compound 25 did not react at all under these conditions. These results indicated that the bulkiness and basicity of the amine werei mportant for this [5+ +2] cycloaddition.N otably, this established sequence including a[5+ +2] cycloaddition readily furnished the ADE ring core bearingt he spiro structure and vicinal quaternary carbon centers from commerciallya vailable materialt hrough eight steps and three purifications using silica gel chromatography.…”
mentioning
confidence: 99%
“…Intramolecular nucleophilic attack of the amine was used to form unstablee naminone 24,w hich was then trapped using CbzCl as ad ienamide 25 in 72 %y ield. Various oxidation conditions, including H 2 O 2 / HCO 2 H, [18] MoO 5 ·pyridine complex, [19] and PhNO, [20] were tested, but compound 25 did not react at all under these conditions. Furthermore, using 3-chloroperoxybenzoic acid (mCPBA) [21] or NBS [22] resulted in the decomposition of startingm aterial 25.…”
mentioning
confidence: 99%